Postseismic deformation following the Mw 7.2, 23 October 2011 Van earthquake (Turkey): Evidence for aseismic fault reactivation - Dogan, Ugur; Demir, Deniz O.; Cakir, Ziyadin; Ergintav, Semih; Ozener, Haluk; Akoglu, Ahmet M.; Nalbant, Suleyman S.; Reilinger, Robert (AMER GEOPHYSICAL UNION, 2014)
Geodetic measurements following the 23 October 2011, M-w=7.2 Van (eastern Turkey) earthquake reveal that a fault splay on the footwall block of the coseismic thrust fault was reactivated and slipped aseismically for more than 1.5years following the earthquake. Although long-lasting aseismic slip on coseismic ruptures has been documented following many large earthquakes, long-lasting, triggered slip on neighboring faults that did not rupture during the earthquake has not been reported previously. Elastic dislocation and Coulomb stress modeling indicate that the postseismic deformation can be adequately explained by shallow slip on both the coseismic and splay fault and is likely driven mostly by coseismic stress changes. Thus, the slip deficit on the shallow section of the coseismic fault indicated by interferometric synthetic aperture radar-based models has been partially filled by aseismic slip, suggesting a lower likelihood for a large earthquake on the shallow section of the Van fault than suggested by previous studies.
Keywords: Van earthquake; GPS; postseismic deformation; afterslip; SLIP; INTERFEROMETRY; MAGNITUDE; EVOLUTION; STRESS; Geology